APPROACH UNDER THE FORM OF SEMIQUANTITATIVE CYTOLOGICAL EVALUATION FOR CHRONIC PHARYNGITIS - Ferrara, Lydia; Naviglio, Daniele; Caruso, Arturo Armone (European Scientific Journal, ESJ, 2014)
In this study, we propose a semi-quantitative evaluation form for diagnosis of chronic pharyngitis based on both subjective and objective parameters. The data collection symptom of patients together with the microscopic evaluation of the cytological specimen allows to diagnose with a high degree of certainty the severity of the inflammatory state of the pharynx. This assessment is certainly very important for the evaluation of therapeutic treatment in relation to the severity of the disease